2022
DOI: 10.3390/plants11101366
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination and Germination of Buckwheat Grains upon Treatment with Oxygen Plasma Glow and Afterglow

Abstract: Buckwheat is an alternative crop known for its many beneficial effects on our health. Fungi are an important cause of plant diseases and food spoilage, often posing a threat to humans and animals. This study reports the effects of low-pressure cold plasma treatment on decontamination and germination of common (CB) and Tartary buckwheat (TB) grains. Both plasma glow and afterglow were applied. The glow treatment was more effective in decontamination: initial contamination was reduced to less than 30% in CB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…They were harvested in 2021 and stored in a dry and dark environment at room temperature until the experiments were performed in 2022. Fungal strains used in these experiments were previously isolated from buckwheat grains in our laboratory, grown in pure cultures, and morphologically and/or molecularly characterised [ 11 , 14 , 35 ], deposited and stored in the fungal bank of the Laboratory for Plant Physiology at the Chair of Botany and Plant Physiology, Department of Biology, Biotechnical faculty, University of Ljubljana. The strains used were: Alternaria alternata (GB002), Aspergillus flavus (GB005), Aspergillus niger (GB006), Cladosporium cladosporioides (GB007), Epicoccum nigrum (GB009), Fusarium fujikuroi (GB011), Fusarium graminearum (GB012), Fusarium oxysporum (GB013), Fusarium proliferatum (GB014), and Fusarium sporotrichioides (GB015) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were harvested in 2021 and stored in a dry and dark environment at room temperature until the experiments were performed in 2022. Fungal strains used in these experiments were previously isolated from buckwheat grains in our laboratory, grown in pure cultures, and morphologically and/or molecularly characterised [ 11 , 14 , 35 ], deposited and stored in the fungal bank of the Laboratory for Plant Physiology at the Chair of Botany and Plant Physiology, Department of Biology, Biotechnical faculty, University of Ljubljana. The strains used were: Alternaria alternata (GB002), Aspergillus flavus (GB005), Aspergillus niger (GB006), Cladosporium cladosporioides (GB007), Epicoccum nigrum (GB009), Fusarium fujikuroi (GB011), Fusarium graminearum (GB012), Fusarium oxysporum (GB013), Fusarium proliferatum (GB014), and Fusarium sporotrichioides (GB015) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After CP treatment, we showed significant changes in the frequency and diversity of naturally occurring fungal colonisers of buckwheat grains [ 14 ]. Furthermore, we also demonstrated that direct exposure to CP (in »glow« mode) is more effective in the decontamination of grains than indirect exposure (»afterglow« mode) [ 35 ]. However, in the research of naturally occurring fungi on grains (natural grain microbiota), the absence of fungal taxa can be attributed to the successful CP decontamination or the absence of fungi.…”
Section: Introductionmentioning
confidence: 99%